Two Isomeric C16 Oxo-Fatty Acids from the Diatom Chaetoceros karianus Show Dual Agonist Activity towards Human Peroxisome Proliferator-Activated Receptors (PPARs) α/γ - Moldes-Anaya, Angel; Sæther, Thomas; Uhlig, Silvio; Nebb, Hilde Irene; Larsen, Terje; Eilertsen, Hans Christian; Paulsen, Steinar Martin (Marine Drugs, 2017)
Source at http://dx.doi.org/10.3390/md15060148 The peroxisome proliferator-activated receptors (PPARs) function as ligand-activated transcription factors that convert signals in the form of lipids to physiological responses through the activation of metabolic target genes. Due to their key roles in lipid and carbohydrate metabolism, the PPARs are important drug targets. However, for several of the PPAR drugs currently in use, adverse side effects have been reported. In an effort to identify compounds from marine organisms that may serve as molecular scaffolds for the development of novel and safer PPAR-targeting drugs, we performed a bioassay-guided screening of organic extracts made from organisms supplied by the Norwegian Biobank of Arctic Marine Organisms (Marbank). Among several interesting hits, we identified two poorly described isomeric oxo-fatty acids from the microalgae Chaetoceros karianus for which we provide the first evidence that they might display dual specificity towards human PPARα and PPARγ. Principal component analysis showed that C. karianus stood out from other Chaetoceros species, both with respect to the metabolic profile and the PPAR activity. The isolation of these compounds holds the potential of uncovering a PPAR pharmacophore with tunable activity and specificity.